PERAN BADAN PERMUSYAWARATAN DESA DALAM MENDORONG GOOD GOVERNANCE DI DESA CIBUNAR KECAMATAN RANCAKALONG KABUPATEN SUMEDANG : - Deden Haria Garmana; Zanzan Yudha Sozidin (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The purpose of this study was to determine the role of the village consultative body in encouraging good governance in Cibunar Village, Rancakalong District, Sumedang Regency. The research method used in this study, namely qualitative research methods. The technique of determining research informants is purpose sampling. Data collection techniques used, namely library research and field studies consisting of observations, interviews, and documentation. The data processing procedure uses data reduction, data display, data conclusion drawing. verification and triangulation. Based on the results of the study, it was concluded that the role of the Cibunar Village Consultative Body could not be said to be good, the Cibunar Village Consultative Body, in terms of administration, could not be said to be good because there were still many obstacles, one of which was the quality of resources that were less than optimal and the understanding of members of the village consultative body towards their duties. and functions are still lacking, describing the role of the Village Consultative Body in encouraging good governance in Cibunar Village, Rancakalong District, Sumedang Regency. To realize democracy and good governance at the village level as aspired to in the law.